Factors influencing students’ intention to enroll at private higher education institution - Somantri, Ace; Zaid, Zaid; Pratondo, Katon; Asmara, Abdullah Qiqi (International Journal of Evaluation and Research in Education (IJERE), 2025)
Intense competition exists amid the rapid growth of universities worldwide and in Indonesia. Often, private higher education is the victim of defeat from competition. Because competitive pressures such as these will undoubtedly lead to reduced revenues, universities are encouraged to increase their student numbers to increase revenues. According to the theory of planned behavior, the intention to carry out certain actions is an essential prerequisite for the strategy’s success. This research examines the factors influencing students to enroll in private, Muhammadiyah contexts, higher education institutions. By involving 572 respondents and using partial least squares structural equation modeling (PLS-SEM) analysis, this research shows that among the factors that influence students’ intention in enrolling in Muhammadiyah Higher Education Institutions are higher education institution image and student characteristics, where both have a positive and significant influence with values (β=0.409; p-value=0.000) and (β=0.461; p-value=0.001).